Asking Skill’s Biology Teacher of Muhammadiyah Senior High School Based on 2013 Curriculum in Klaten Year 2014/2015 - Praditya Panji Prabowo; Hariyatmi Hariyatmi (Universitas Sebelas Maret, 2015)
Asking skill is a verbal greeting to stimulate students and increase thinking ability. The purpose of the research was to find out the skills of biology teachers of Muhammadiyah Senior High School based on 2013 curriculum in Klaten Regency academic year 2014/2015. This research was a descriptive qualitative research. Data analyzed by descriptive statistics. Observation and interview in 4 Senior High School Muhammadiyah were used to collect the data. The results showed the ability of asking skill in two categories. The average result of observation of overall category is 50.86%. The results of A teacher (47.97%), B teacher 54,91(%), C teacher (52.38%), and D teacher (57,07%). The result from interview are 58,33% teachers very well ask skills and 16.67% quite well.Keywords: Asking ability, types of questions